Variable Sound Insulation Structure with MFC Elements - GÓRSKI, Paweł; KOZUPA, Michał (Archives of Acoustics, 2012)
Additional sound sources are used as actuators in the vast majority of active noise reduction systems. One of the possible opportunities to extend the field of applications of active noise reduction systems is using active structures of variable sound insulation. The paper presents an analysis of ways of reducing noise with a structure of variable sound insulation consisting of a metal plate, active elements (Macro Fiber Composite), and a control system. The paper presents results of acoustic radiation simulations and measurements of sound intensity generated by the structure under the influence of stimulation by an acoustic wave. Simulations of mechanical vibrations and acoustic radiation for the plate were performed with the finite element method and ANSYS software. Simulation results made it possible to select locations for gluing the active elements and sensors. Analyses of the sound pressure level in the space to which the plate is radiating made it possible to determine dominant frequencies in the characteristics and, as a result, indicate vibration modes that can be reduced. Sound intensity measurements were performed with a three-way probe of USP mini Microflown. Results of simulations and measurements show that it is possible to achieve an improvement of the insulating power of a metal plate by approx. 10 dB.